Gestational age-dependent changes in human ductus arteriosus: A cadaveric histomorphometric and developmental analysis - Adhikari, Purnima; Punja, Rohini; Kalthur, Sneha Guruprasad (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The ductus arteriosus (DA) is a critical vascular structure in fetal circulation, shunting blood from the pulmonary artery to the aorta. The study investigates the histomorphometric  characteristics of the ductus arteriosus (DA) in human fetuses, exploring its developmental changes across gestational ages.Methods: This cross-sectional observational study examined 20 human fetal cadavers ranging from 17 to 37 weeks gestation, stratified into two groups: Group I (17th-24th week, n=10) and Group II (25th-37th week, n=10). Gross morphometric analysis included measurements of DA length, diameter at aortic and pulmonary ends, and angular orientation relative to the aorta. Histological examination involved H&E staining, with quantitative analysis of tunica media thickness.Results: Gross anatomical measurements showed significant growth of DA from Group I to Group II. Angular measurements showed more modest changes, with the upstream angle increasing from 52.9° ± 3.5° to 61.0° ± 4.8° and downstream angle from 92.9° ± 7.9° to 103.8° ± 5.2°, exhibiting weak correlations with gestational age. Histologically, DA demonstrated a typical muscular artery structure. Group II fetuses exhibited more prominent internal and external elastic laminae. The tunica media showed notable differences, with Group I displaying a predominance of fibroblasts, while Group II fetuses had a thicker tunica media with more organized concentric lamellae.Conclusions: The relative stability of DA's angular orientation suggests evolutionary optimization of fetal hemodynamics. The progressive organization and thickening of the tunica media, along with the development of elastic laminae, indicate a structural maturation process likely underpinning the DA's functional capabilities.